Retinal vascular calibres: Risk factors and methodological aspects of retinal vascular imaging. The Tromsø Eye Study – a part of the Tromsø Study. - Hanno, Therese von (UiT Norges arktiske universitet, 2014)
The papers of this thesis are not available in Munin: 1. von Hanno T, Bertelsen G, Sjølie AK, Mathiesen EB.: 'Retinal vascular calibres are significantly associated with cardiovascular risk factors: the Tromsø Eye Study', Acta Ophthalmologica (2013), Online ahead of print. Available at http://dx.doi.org/10.1111/aos.12102 2. von Hanno T, Bertelsen G, Broderstad AR, Wilsgaard T, Mathiesen EB.: 'Serum ferritin and hemoglobin are independently associated with wider retinal venular caliber. The Tromsø Study 2001-2008', Investigative Ophthalmology & Visual Science (2013), vol. 54(10):7053-7060. Available at http://dx.doi.org/10.1167/iovs.13-12204 3. von Hanno T, Sjølie AK, Mathiesen EB.: 'Retinal vascular calibre and response to light exposure and serial imaging', Acta Ophthalmologica (2013), Online before print. Available at http://dx.doi.org/10.1111/aos.12213 Cardiovascular disease is a major cause of death and morbidity in developed countries. The eye offers a unique window to the study of the microvasculature in vivo, which has been less investigated than the macrovasculature. We wanted to investigate the relationship between the traditional cardiovascular risk factors and retinal vascular calibres. Further, iron is a proposed cardiovascular risk factor and we wanted to investigate whether measures of iron stores and hemoglobin are related to retinal vascular calibre. The two first papers in this thesis are based on data from the Tromsø Study. We have measured the diameter of the retinal arterioles and venules on retinal images from 6353 participants of the sixth survey of the Tromsø Study (Tromsø 6, 2007-2008). We found that blood pressure and smoking were the factors with the most pronounced effect on the retinal vascular calibre. Blood pressure and age were associated with narrower retinal vessels and mainly affecting arteriolar calibre. Smoking, overweight (body mass index) and unfavourable lipid-profile were associated with wider retinal vessels, mainly affecting venular calibre. The effect of low HDL ...